2014
DOI: 10.1371/journal.pone.0087300
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Roles for the Glutathione Reductase, Thioredoxin Reductase and Thioredoxin Peroxidase-Encoding Genes of Magnaporthe oryzae during Rice Blast Disease

Abstract: Understanding how pathogenic fungi adapt to host plant cells is of major concern to securing global food production. The hemibiotrophic rice blast fungus Magnaporthe oryzae, cause of the most serious disease of cultivated rice, colonizes leaf cells asymptomatically as a biotroph for 4–5 days in susceptible rice cultivars before entering its destructive necrotrophic phase. During the biotrophic growth stage, M. oryzae remains undetected in the plant while acquiring nutrients and growing cell-to-cell. Which fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 42 publications
1
74
0
Order By: Relevance
“…The thioredoxin system contains thioredoxins (Trx), and the NADPH-dependent enzyme thioredoxin reductase (TrxR) (Lu and Holmgren, 2014;Fernandez and Wilson, 2014). Thioredoxins are ubiquitous redox proteins containing cysteine residues that are reversibly redox active, cycling between oxidized disulfide (Trx-S 2 ) and reduced dithiol [Trx-(SH) 2 ] in a TrxR dependent manner (Holmgren, 1989;Zhang et al, 2016).…”
Section: Transcriptional Control Of Ros Catabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…The thioredoxin system contains thioredoxins (Trx), and the NADPH-dependent enzyme thioredoxin reductase (TrxR) (Lu and Holmgren, 2014;Fernandez and Wilson, 2014). Thioredoxins are ubiquitous redox proteins containing cysteine residues that are reversibly redox active, cycling between oxidized disulfide (Trx-S 2 ) and reduced dithiol [Trx-(SH) 2 ] in a TrxR dependent manner (Holmgren, 1989;Zhang et al, 2016).…”
Section: Transcriptional Control Of Ros Catabolismmentioning
confidence: 99%
“…The cell-intrinsic glucose-6-phosphate/ NADPH-sensing Tps1 enzyme mediates activation of the thioredoxin and glutathione systems in M. oryzae. Tps1 controls the expression of NADPH-dependent enzymes-including those of the thioredoxin and glutathione antioxidation system-in response to NADPH availability while balancing the production of NADPH with glucose-6-phosphate availability, thus providing molecular links between primary metabolism and antioxidation during host infection (Fernandez et al, 2012;Fernandez and Wilson, 2014;Wilson et al, 2010). Building on this concept, a more recent study in M. oryzae showed that the NMO2 gene, encoding a nitronate monooxygenase enzyme catalyzing oxidative denitrification of nitroalkanes, is carbon and nitrogen responsive, regulated by Tps1, and required for axenic growth on nitrate media (Marroquin-Guzman et al, 2017).…”
Section: Hemibiotrophs: Linking Redox Homeostasis With Primary Metabomentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] The M. oryzae glucose-6-phosphate (G6P) sensor, Tps1, regulates carbon metabolism and connects glucose availability 17 to glutathione-dependent antioxidation and the establishment of biotrophy. 18 Other examples linking fungal metabolic regulation and plant defense suppression are not known. We hypothesized that nitrogen-regulated processes might also contribute to the colonization of rice cells by M. oryzae.…”
Section: Authorsmentioning
confidence: 99%
“…Function loss of a Trr homologue in Magnaporthe oryzae resulted in attenuated ability to grow in rice cells and a failure to produce spreading necrotic lesions on the leaf surface (Fernandez and Wilson 2014). Deletion of trr1 from Botrytis cinerea impaired the fungal virulence and antioxidant capability due to enhanced H 2 O 2 production and retarded growth (Viefhues et al 2014).…”
Section: Introductionmentioning
confidence: 99%